Galvanic Restructuring of Exsolved Nanoparticles for Plasmonic and Electrocatalytic Energy Conversion (Small 29/2022). Issue 29 (21st July 2022) - Kang, Xiaolan; Reinertsen, Vilde Mari; Both, Kevin Gregor; Galeckas, Augustinas; Aarholt, Thomas; Prytz, Øystein; Norby, Truls; Neagu, Dragos; Chatzitakis, Athanasios
Abstract : Photoelectrochemical Water Splitting In article number 2201106, Athanasios Chatzitakis and co‐workers combine in situ metal exsolution and the galvanic replacement reaction for the synthesis of advanced catalysts for diverse energy conversion applications. Exsolved Ni nanoparticles are galvanically restructured and a wealth of bimetallic nanostructures are facilely synthesized. Among them are well adhered and supported AuNi antenna‐reactor nanoconfigurations with improved plasmonic activity for photoelectrochemical water splitting in alkaline conditions.